Diode-bridge enclosed one switch three-phase power factor corrected (PFC) Ĉuk rectifier - Abedin, Amina Hasan; Uddin, Mohammad Nasir; Islam, Samia M.Naeemul; Choudhury, Mohammad Ali A.Shoukat; Bashar, Khandaker Lubaba (© 2017 IEEE, 2018)
This conference paper was presented in the 2017 IEEE International Conference on Industrial Technology, ICIT 2017; Hilton TorontoToronto; Canada; 23 March 2017 through 25 March 2017 [© 2017 IEEE ] The conference paper's definite version is available at: http://doi.org/10.1109/ICIT.2017.7913062